2004
DOI: 10.1128/mcb.24.12.5496-5509.2004
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Cell Signaling, Chromatin Remodeling, Histone Modifications, and Regulator Recruitment in Human Matrix Metalloproteinase 9 Gene Transcription

Abstract: Transcriptional activation of eukaryotic genes depends on the precise and ordered recruitment of activators, chromatin modifiers/remodelers, coactivators, and general transcription factors to the promoters of target genes. Using the human matrix metalloproteinase 9 (MMP-9) gene as a model system, we investigated the sequential assembly and dynamic formation of transcription complexes on a human promoter under the influence of mitogen signaling. We find that, coincident with activation of the MMP-9 gene, activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
147
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 44 publications
(56 reference statements)
12
147
1
1
Order By: Relevance
“…6B), indicating that p8 is capable of associating with the mmp9 and mmp13 promoters in different cell types. The induction by TNF of mmp9 and mmp13 is mediated in part by the AP-1 transcription factor (1,24,34,36,38). Consistent with this, we also observed that recombinant p8 associates with chromatin that contains the AP-1 component c-Jun (Fig.…”
Section: Vol 27 2007 P8 Gene Induction Hypertrophy and Mmp Expresupporting
confidence: 73%
See 3 more Smart Citations
“…6B), indicating that p8 is capable of associating with the mmp9 and mmp13 promoters in different cell types. The induction by TNF of mmp9 and mmp13 is mediated in part by the AP-1 transcription factor (1,24,34,36,38). Consistent with this, we also observed that recombinant p8 associates with chromatin that contains the AP-1 component c-Jun (Fig.…”
Section: Vol 27 2007 P8 Gene Induction Hypertrophy and Mmp Expresupporting
confidence: 73%
“…S5 in the supplemental material). By contrast, induction of mmp9, which does require AP-1 (24), is augmented by p8. Taken together, these findings suggest that p8 is not a sequence-specific DNA binding protein per se, nor does it likely act at cis elements of sequence-specific transcription factors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The proximal (À73/ À79) AP-1 site (TGAGTCA) is well conserved among human, rat, and mouse MMP9 promoters, and has high sequence homology to the TGF-b responsive elements, TGACTCA and TGAGTTCA, in human MMP13 and rat PAI-1 promoters, respectively (Uria et al, 1998;Guo et al, 2005). Given that both proximal AP-1 and NF-kB cis-elements are essential for mitogeninduced MMP9 upregulation (Ma et al, 2004), proximal AP-1 and NFkB mutants of MMP9 promoter were further tested for TGF-b-mediated response. Matrix metalloproteinase 9 promoter with a specific mutation in Figure 3 Cited2 enhances Smad3/p300-mediated transcription through p300/Cited2/Smad3 interaction.…”
Section: Cited2 Enhances Tgf-b-mediated Mmp9 Promoter Reporter Activitymentioning
confidence: 99%